Comparison of the late H1 histone genes of the sea urchins Lytechinus pictus and Strongelocentrotus purpuratus. - Knowles, J A (1986)
We have isolated and sequenced a gene encoding a late H1 histone subtype from the sea urchin species L. pictus. The primary structure of the late H1 subtype encoded by this gene is 209 amino acids in length, and has a net positive charge of 67. This gene is present in a single copy per haploid genome and encodes an mRNA of 752 nucleotides. Late H1 transcripts are detected in the unfertilized egg and are most prevalent in gastrulating embryos. Comparison of 375 bp of 5' flanking sequences of the L. pictus late H1 gene and the H1-gamma gene of a distantly related sea urchin species, S. purpuratus, reveals large blocks of sequences that are identical between the two genes. To determine if these conserved 5' sequences are present in other members of the sea urchin H1 gene family, the analogous region of S. purpuratus H1-alpha, an early H1 gene, was sequenced. The homology between the flanking sequences of the early and late families was limited to consensus sequences which are found upstream of all H1 genes. The possible regulatory implications of these findings are discussed.